1998
DOI: 10.1051/forest:19980112
|View full text |Cite
|
Sign up to set email alerts
|

Scaling xylem sap flux and soil water balance and calculating variance: a method for partitioning water flux in forests

Abstract: -To partition evapotranspiration between canopy and subcanopy components in a 12-m-tall Pinus taeda forest and to assess certain aspects of environmental regulation of canopy transpiration, we quantified water flux in a forest using three approaches: 1) measuring water flux in xylem of trees, and scaling to stand transpiration of canopy trees (E C ); 2) measuring soil water content and saturated conductivity, and modeling drainage to estimate total evapotranspiration (E T ) during rainless days based on a loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
182
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(193 citation statements)
references
References 35 publications
10
182
1
Order By: Relevance
“…Spruce 2 had two large branches, just above the Granier measuring point, which may have also affected the flow pattern as compared to Spruce 1, where there were no large branches near the measuring point. The radial variation in sapflow density was in the same range as those found in several studies on pine and spruce [6,25,34,37]. A sensor that covered the whole sapwood depth, and integrated the variation in sapflow, would probably best account for the radial variations in sapflow density.…”
Section: Radial Variation Of Granier Measurementssupporting
confidence: 62%
“…Spruce 2 had two large branches, just above the Granier measuring point, which may have also affected the flow pattern as compared to Spruce 1, where there were no large branches near the measuring point. The radial variation in sapflow density was in the same range as those found in several studies on pine and spruce [6,25,34,37]. A sensor that covered the whole sapwood depth, and integrated the variation in sapflow, would probably best account for the radial variations in sapflow density.…”
Section: Radial Variation Of Granier Measurementssupporting
confidence: 62%
“…5). Such summer droughts are common in the region (Oren et al 1998a, Ellsworth 1999. Again, the instantaneous scatter in modelled C i /C a was sufficiently large and indicated that processes affecting the dynamics of C i /C a were not resolved by all closure models, at least with their static parameters.…”
Section: Model Assessment With Independent Parametersmentioning
confidence: 82%
“…, equals E L only if J S represents the spatially weighted mean flux (Oren et al 1998a). Sap flux density was measured with a Granier-type sensor composed of a heated (constant heat flow) and unheated thermocouple pair connected in opposition to measure temperature difference, as described by Granier (1987).…”
Section: Methodsmentioning
confidence: 99%
“…Measured sap flux (J S , kg H 2 O m -2 sapwood s -1 ) in the xylem of trees is increasingly used to estimate G S (Köstner et al 1992;Granier and Loustau 1994;Phillips and Oren 1998;Oren et al 1998aOren et al , 1998b, based on the assumption that J S scaled by A S :A L is equal to transpiration rate per unit of leaf area (E L ). Thus, G S for conifers or other species with small leaves (Landsberg 1986;Phillips and Oren 1998;Ewers and Oren 2000) can be calculated using the function (modified from Monteith and Unsworth 1990): (2) where G S is the canopy stomatal conductance for water vapour (m s -1 ), γ is the psychrometric constant (kPa·K -1 ), λ is the latent heat of vaporization (J·kg -1 ), ρ is the density of air (kg·m -3 ), c p is the specific heat of air at constant pressure (J·kg -1 K -1 ), and D is the vapor pressure deficit (kPa).…”
Section: Methodsmentioning
confidence: 99%